MTsS IT Kapau Kab.Agam is Hosting a Workshop on the Use of Adobe Photoshop and Kvi Soft in the Creation of Flip-Book-Based Learning Modules - Rudi Pranata; Refika Mastanora (Jurnal Masyarakat Religius dan Berwawasan, 2022)
This dedication is motivated by the lack of optimal learning and teaching processes for students at school in receiving the material presented by the teacher. Since the pandemic, MAS TI students in Agam Regency have felt bored because the method used by Mr/Mrs Teachers must be online, while MAS teachers in Agam Regency are still relatively weak in IT knowledge. So the IAIN Batusangkar Service Team seeks to provide assistance for teachers to utilize IT in designing learning media that is attractive to students. From the results of the assistance, it was described that 35 participants consisted of 30 people who met the eligibility requirements for the content of teaching materials, 33 people who met the language eligibility requirements, and 25 people who met the eligibility requirements for presentation. This diversity is influenced by the teacher's ability to manage electronic teaching materials, namely the use of design applications such as Adobe Photoshop and KVI Soft, with regular training from practitioners in providing knowledge of developing teaching materials, of course, will further improve the ability of teachers. In the workshop activities carried out it consisted of 20 people aged 25-40 years and the rest were over 40 years old, this also affected teacher productivity in developing IT-based teaching materials.